Pengaruh Budaya Organisasi,Kompensasi, Dan Etos Kerja Terhadap Kinerja Karyawan Hotel Ratna Syariah Kota Probolinggo - Ilyas Maulana Maulana; Joni Hendra; Dedi Joko Hermawan (Universitas Panca Marga, 2024)
The purpose of this research is to determine the influence of organizational culture, compensation and work ethic on employee performance at the Ratna Syariah Hotel, Probolinggo City. Hotel Ratna Syariah Probolinggo City as a provider of accommodation services must of course have good performance in serving customers. The data collection method used saturated sampling, and obtained 48 respondents and a linear regression analysis tool using the SPSS 26 application. The methods of collecting information used in the research were: interviews, documentation and questionnaires. The results of testing Organizational Culture, Compensation, and Work Ethic partially influence employee performance.